The first records of Microprosthema pernambucensis (Bochini, Cunha, Terossi & Almeida, 2020) and Odontozona addaia Pretus, 1990 from the tropical eastern Atlantic (Decapoda: Stenopodidea) - Grave, Sammy De; Anker, Arthur (Zootaxa, 2024)
Two species of stenopodidean shrimps are newly recorded from the tropical eastern Atlantic, each representing considerable extensions to their previously known biogeographical ranges. The shrimp genus Chicosciencea Bochini, Cunha, Terossi & Almeida, 2020, is confirmed as a junior synonym of Microprosthema Stimpson, 1860. Microprosthema pernambucensis (Bochini, Cunha, Terossi & Almeida, 2020), previously only known from northeastern Brazil, is reported for the first time from the tropical eastern Atlantic based on material collected in subtidal lava tubes on the coast of Sal, Cabo Verde, and re-illustrated in view of the limited original description. Odontozona addaia Pretus, 1990, previously only known from the Mediterranean Sea, is herein reported from the Atlantic Ocean proper, based on specimens from the same habitat, also in Cabo Verde.